IMPLEMENTASI MODEL PBL BERBASIS EKSPERIMEN UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH PADA PEMBELAJARAN IPAS KELAS V SD - Aminatuz Zahroh, Nuril; Julianto; Ceffiriana, Paramita; Santoso, Hadi; Hidayati, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by students who found it difficult to connect theory with real-life applications in solving problems. This results in a lack of motivation and interest in solving problems and reduces their ability to apply the concepts they have learned. This problem occurs because the learning strategy used by the teacher is not centered on students by directly involving them in proving a theory being studied and connecting it contextually in everyday life. So to solve this problem, it is necessary to use the right strategy through problem-based learning, which invites students to find problems that are close to their lives. This research aims to improve problem-solving skills through an experiment-based PBL model. This research uses classroom action research using a pre-cycle and two research cycles. In the precycle, the results of diagnostic tests showed that students' problem solving was 33% complete. It shows that it has not met the completeness category of 50% of the number of students. So cycle 1 was carried out using an experimental-based PBL model, which showed problem-solving completeness results of 39%. In cycle 1, there has been an increase, but it is not significant and does not meet the specified category of completeness. So it is necessary to implement cycle 2 with improvements to the treatment and modification of the worksheets used. In cycle 2, the problem-solving completeness category was achieved, namely 82% of the total number of students. From these results, it can be shown that the experimentalbased PBL model can improve students' problem-solving skills.